A novel multi-objective off-board EV charging station for smart homes - Monteiro, Vítor Duarte Fernandes (2018)
A novel multi-objective off-board EV charging station (EVCS) for smart homes is proposed, where the option to integrate a set of functionalities in a single equipment for the smart grid power management is a distinguishing contribution. The EVCS is carefully described along the paper, where its attractive functionalities are: (a) Direct interface with the EV battery, permitting to achieve a flexible grid-to-vehicle (G2V) and vehicle-to-grid (V2G) operation, according to the demand response strategy of the smart grid; (b) Operation as a smart active power conditioner independently of the EV presence; (c) Operation as a reactive power compensator, agreeing to the requirements of the power grid. These functionalities allow to enhance the power quality points in smart homes and grids. The control algorithm of the EVCS is meticulously defined according to the smart home control and the smart grid necessities, aiming to accomplish with the aforementioned functionalities. This paper offering an experimental validation, obtained with a developed prototype, which corroborates the attractiveness of the multi-objective EVCS for smart homes and grids.